Motivated state control in larval zebrafish: behavioral paradigms and anatomical substrates. (2nd April 2016) - Horstick, Eric J.; Mueller, Thomas; Burgess, Harold A.
Abstract: Over the course of each day, animals prioritize different objectives. Immediate goals may reflect fluctuating internal homeostatic demands, prompting individuals to seek out energy supplies or warmth. At other times, the environment may present temporary challenges or opportunities. Homeostatic demands and environmental signals often elicit persistent changes in an animal's behavior to meet needs and challenges over extended periods of time. These changes reflect the underlying motivational state of the animal. The larval zebrafish has been established as an effective genetically tractable vertebrate system to study neural circuits for sensory-motor reflexes. Fewer studies have exploited zebrafish to study brain circuits that control motivated behavior. In part this is because appropriate conceptual frameworks, anatomical knowledge, and behavioral paradigms are not yet well established. This review sketches a general conceptual framework for studying motivated state control in animal models, how this applies to larval zebrafish, and the current knowledge on neuroanatomical substrates for state control in this model.